Stan Napięcia Tarczy Kołowej Obciążonej Wewnętrznymi Siłami Skupionymi - Szelągowski, F. (Engineering Transactions, 1958)
This paper is devoted to the derivation of equations determining thestresses Rθ, Rr, θθ at any point of a circular disc subjected to tension by two concentrated forces equidistant from the centre of the disc.